2021
DOI: 10.1186/s12884-021-03928-w
|View full text |Cite
|
Sign up to set email alerts
|

Euglycaemic ketoacidosis in pregnant women with COVID-19: two case reports

Abstract: Background Euglycaemic ketoacidosis (EKA) is an infrequent but serious condition which usually follows a period of starvation, severe vomiting or illness in individuals with or without diabetes. Ketoacidosis is associated with materno-fetal morbidity and mortality necessitating prompt diagnosis and management. Physiological increases in insulin resistance render pregnancy a diabetogenic state with increased susceptibility to ketosis. COVID-19 is associated with worse clinical outcomes in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
(32 reference statements)
0
18
0
1
Order By: Relevance
“…Among the included studies, 11 reported DKA and COVID-19 in children [ 8 , 11 , 22 , 30 , 34 , 44 , 45 , 56 , 61 , 66 , 72 ], 56 reported DKA and COVID-19 in adults [ 9 , 10 , 12 21 , 23 , 25 29 , 31 33 , 35 43 , 46 55 , 57 – 60 , 62 65 , 67 71 , 73 75 ], and only 1 study reported DKA and COVID-19 in both children and adults [ 24 ]. There were 54 case report [ 8 12 , 14 , 16 , 17 , 19 23 , 25 27 , 29 42 , 44 51 , 53 58 , 60 , 61 , 64 , 66 , 67 , 69 , 71 , 72 , 74 , 75 ], 10 case series [ 13 , 15 , 28 , 43 , 58 , 59 , 62 , 63 , 70 , 73 ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the included studies, 11 reported DKA and COVID-19 in children [ 8 , 11 , 22 , 30 , 34 , 44 , 45 , 56 , 61 , 66 , 72 ], 56 reported DKA and COVID-19 in adults [ 9 , 10 , 12 21 , 23 , 25 29 , 31 33 , 35 43 , 46 55 , 57 – 60 , 62 65 , 67 71 , 73 75 ], and only 1 study reported DKA and COVID-19 in both children and adults [ 24 ]. There were 54 case report [ 8 12 , 14 , 16 , 17 , 19 23 , 25 27 , 29 42 , 44 51 , 53 58 , 60 , 61 , 64 , 66 , 67 , 69 , 71 , 72 , 74 , 75 ], 10 case series [ 13 , 15 , 28 , 43 , 58 , 59 , 62 , 63 , 70 , 73 ...…”
Section: Resultsmentioning
confidence: 99%
“…The median random blood glucose level, HbA1c, pH, bicarbonate, and anion gap in all included patients at presentation were 507 mg/dl [IQR 399–638 mg/dl], 11.4% [IQR 9.9–13.5%], 7.16 [IQR 7.00–7.22], 10 mmol/l [IQR 6.9–13 mmol/l], and 24.5 mEq/l [18–29.2 mEq/l]; respectively. Five patients had blood glucose < 250 mg/dl at presentation (euglycemic DKA) [ 16 , 53 , 65 , 71 ]; one was on SGLT2 inhibitor medication [ 16 ] while seven patients had gestational diabetes mellitus [ 53 , 65 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations